ON COLLECTIONS OF GARLIC ODOROUS MARASMIELLUS IGNOBILIS (BERK. & BR.) SINGER FROM INDONESIA - Atik Retnowati (Floribunda, 2011)
Atik Retnowati. On Collections of Garlic Odorous Marasmiellus ignobilis (Berk. & Br.) Singer from Indonesia. Floribunda 4(2): 57–61. — Marasmiellus ignobilis (Berk. & Br.) Singer was collected from three sites in Indonesia, i.e Bogor Botanical Garden, Mount Halimun-Salak National Park and Pohen hill (Bedugul, Bali).This is the first report on the occurence of Marasmiellus with garlic odor in Indonesia